Micro-scaffolded peer consultation in hybrid literature classes: Enhancing analytical skills through the Seed–Pollinate–Synthesize (SPS) cycle - Ronald M. Quileste; Norman C. Calib-og; Judha Mae E. Abalde; Irish Vine S. Caayupan; Marvic Niña L. Kiseo; Melce Mae L. Salarda; Jessa Joyce I. Tamiok (CV. Yudhistt Fateeh, 2026)
This explanatory sequential mixed-methods action research investigated student disengagement in literary analysis within a hybrid Grade 12 Humanities and Social Sciences classroom in the Philippines. A total of 28 students from two Grade 12 HUMSS sections at Xavier University Senior High School participated, selected through convenience sampling from enrolled students who provided informed consent. A 20-minute micro-scaffolded intervention—the Seed–Pollinate–Synthesize (SPS) cycle—was implemented asynchronously through Microsoft Teams. Students collaborated in fixed groups: first annotating a figurative device individually, then cross-questioning peers in a shared document, and finally co-authoring one justified textual insight. Pre-intervention diagnostics revealed an advanced baseline with limited evaluative depth. Post-intervention results, collected via identical pre- and post-tests and analyzed using the Wilcoxon Signed-Rank test, showed significant improvement with a large effect size (r = .68). Thematic coding of chat transcripts and teacher reflection logs through the Cognitive–Social–Metacognitive (CSM) framework identified cognitive discourse as the driver of evidence use, social exchanges as the anchor of inclusion, and metacognitive prompts as the regulator of synthesis. The SPS cycle introduces a replicable, low-resource protocol that transforms passive hybrid reading into active peer consultation. Digital traces provide transparent evidence of scaffolding within the Zone of Proximal Development, while teacher reflections confirm feasibility amid real-world connectivity constraints. Limitations include its single-module scope, absence of a control group, and strand-specific sampling. Future research will extend implementation across modules, strands, and time frames to test durability and transferability. Overall, the SPS cycle supports scalable critical literacy aligned with global quality education goals, offering teachers a practical framework to elevate analytical discourse in resource-constrained hybrid environments.